(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Multiple studies have demonstrated that the yield of imaging for distant metastatic disease is low in patients with early-stage breast cancer without signs and symptoms of metastatic disease. So, a study was carried out to assess the clinical significance and usefulness of staging investigations in newly diagnosed early-stage breast cancer patients. Materials and method: A retrospective review of medical records of 171 patients with early-stage (stage I & II) breast cancer referred to the Tumor Board & Radiation Oncology department of NICRH and one private hospital after having surgery & adjuvant chemotherapy during the two-year period (January 2019-December 2020), were performed. The staging investigations the patients underwent perioperatively and the value of those in detecting metastasis were evaluated. Result: All patients had chest radiography and routine blood tests performed preoperatively. Postoperative chest radiography evaluation in various frequencies were done in 156 (91.22%) patients. CT scans of the chest were performed in 13 patients (7.6%). One patient (0.64%), who had complained of cough was diagnosed with pulmonary metastasis after evaluation. An ultrasonogram (USG) of the whole abdomen was done preoperatively in 135 patients (78.9%) & postoperatively and subsequently in 162 patients (94.7%) in various frequencies and CT scans of the abdomen were done in 7 patients (4.1%). No metastasis was detected by USG or CT scan of the abdomen. Bone scan was done in 53 patients (31%). Four patients (4/53) were diagnosed with bony metastases out of which 2 had symptoms of bone pain. Routine bone scan can picked up 2(3.7%) bone metastases in asymptomatic patients. Conclusion: Staging investigations for distant metastases in newly diagnosed early-stage breast cancer patients in the absence of signs and symptoms of metastatic disease have low yield, not evidence-based, not cost-effective and thus not recommended. J Bangladesh Coll Phys Surg 2024; 42: 38-42